The Forests of Ajmer State - Nagdev, D. P. (Indian Forester, 1954)
The xerophytic forests of Ajmer State consisting of 46,688 acres lying in the arid zone, comprised about two per cent of the land area till September 1948 when the forest development schemes started functioning under which 67,502 acres more have been reserved to-date. The newly acquired areas are being gradually and systematically improved by adopting various artificial regeneration methods, rotational grazing and rigid protection. Soil conservation and wild-life preservation work is being attended to. The villagers contributing land for formation of forests get the two-third to full of from net forest profits - a most conspicuous and interesting aspect of the administration of the State's forests.